When Are Adverse Outcome Pathways and Associated Assays "Fit for Purpose" for Regulatory Decision‐Making and Management of Chemicals?. (17th July 2019) - Coady, Katie; Browne, Patience; Embry, Michelle; Hill, Thomas; Leinala, Eeva; Steeger, Thomas; Maślankiewicz, Lidka; Hutchinson, Tom
ABSTRACT: There have been increasing demands for chemical hazard and risk assessments in recent years. Chemical companies have expanded internal product stewardship initiatives, and jurisdictions have increased the regulatory requirements for the manufacture and sale of chemicals. There has also been a shift in chemical toxicity evaluations within the same time frame, with new methodologies being developed to improve chemical safety assessments for both human health and the environment. With increased needs for chemical assessments coupled with more diverse data streams from new technologies, regulators and others tasked with chemical management activities are faced with increasing workloads and more diverse types of data to consider. The Adverse Outcome Pathway (AOP) framework can be applied in different scenarios to integrate data and guide chemical assessment and management activities. In this paper, scenarios of how AOPs can be used to guide chemical management decisions during research and development, chemical registration, and subsequent regulatory activities such as prioritization and risk assessment are considered. Furthermore, specific criteria (e.g., the type and level of AOP complexity, confidence in the AOP, as well as external review and assay validation) are proposed to examine whether AOPs and associated tools are fit for purpose when applied in different contexts. Certain toxicity pathways are recommended as priority areas for AOP research and development, and the continued use of AOPs and defined approaches in regulatory activities are recommended. Furthermore, a call for increased outreach, education, and enhanced use of AOP databases is proposed to increase their utility in chemicals management. Integr Environ Assess Manag 2019;15:633–647. © 2019 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) Key Points: Specific criteria are proposed for evaluating whether adverse outcome pathways (AOPs) and associated assays are fit for purpose in various chemical management scenarios. Case studies are provided to illustrate how AOPs may be applied in various stages of chemical management and decision making. In the future, priority should be given to developing AOPs that are clear and concise as well as relevant to regulatory endpoints and a large number of chemicals and associated modes of action. Adverse outcome pathways are useful in many different chemical management scenarios, and AOPs should continue to be used in regulatory efforts such as defined approaches.